2007
DOI: 10.1093/brain/awm260
|View full text |Cite
|
Sign up to set email alerts
|

The β-amyloid protein of Alzheimer's disease increases neuronal CRMP-2 phosphorylation by a Rho-GTP mechanism

Abstract: Neuritic abnormalities are a major hallmark of Alzheimer's disease (AD) pathology. Accumulation of beta-amyloid protein (Abeta) in the brain causes changes in neuritic processes in individuals with this disease. In this study, we show that Abeta decreases neurite outgrowth from SH-SY5Y human neuroblastoma cells. To explore molecular pathways by which Abeta alters neurite outgrowth, we examined the activation and localization of RhoA and Rac1 which regulate the level and phosphorylation of the collapsin respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 117 publications
8
132
1
Order By: Relevance
“…Neurite outgrowth and retraction are processes tightly regulated by cytoskeletal dynamics. Previous studies reported that Ab fibrils reduce neurite outgrowth via activation of RhoA in a neuroblastoma cell line 23 and in hippocampal neurons 24 . Ab is released extracellularly on cleavage of amyloid precursor protein at the plasma membrane or in endosomes, and the monomeric form is present in the extracellular milieu before aggregation might take place.…”
Section: Resultsmentioning
confidence: 96%
“…Neurite outgrowth and retraction are processes tightly regulated by cytoskeletal dynamics. Previous studies reported that Ab fibrils reduce neurite outgrowth via activation of RhoA in a neuroblastoma cell line 23 and in hippocampal neurons 24 . Ab is released extracellularly on cleavage of amyloid precursor protein at the plasma membrane or in endosomes, and the monomeric form is present in the extracellular milieu before aggregation might take place.…”
Section: Resultsmentioning
confidence: 96%
“…RhoA mislocalization can also be seen in the human amyloid precursor protein (hAPP) Tg2576 (Swedish mutation) AD mouse model, which shows decreased levels in synapses but increased levels in dystrophic neurites [30]. At 12-18 months of age, these mice have also been reported to have significantly increased RhoA levels and decreased Rac1 levels in the brain [31]. Our recent studies in the hAPP J20 (Swedish and Indiana mutations) AD mouse model show a strong correlation between dendritic spine loss and behavioral deficits with a significant increase in RhoA activity [32].…”
Section: Rho-guanosine Triphosphatases At the Center Of Ad Pathologymentioning
confidence: 99%
“…In vitro studies in cultured cells also reflect these changes. Aβ oligomers trigger a significant increase in RhoA activity in both SY5Y cells and in cultured hippocampal neurons [31][32][33][34]. Cdc42 and Rac1 levels have been reported to be elevated in select neuronal populations in AD brains compared with age-matched controls and have been proposed to perhaps play a role in activating cell cycle-related genes [35].…”
Section: Rho-guanosine Triphosphatases At the Center Of Ad Pathologymentioning
confidence: 99%
“…The small Rho GTPase RhoA and its major effector Rho kinase (ROCK) could be firm partners of NO-directed synapse elimination during neuropathological progression: (1) RhoA/ ROCK mediates neurite retraction, preventing axon growth initiation, and dendrite retraction in different neuronal types in culture (Luo, 2000(Luo, , 2002; (2) activity of ROCK and protein kinase G (PKG), a downstream NO/cGMP effector, mediates semaphorin 3A-induced growth cone collapse (Dontchev and Letourneau, 2002); (3) RhoA upregulation occurs in neurons surrounding amyloid plaques and an increase in phosphorylation of RhoA/ROCK substrates is involved in ␤-amyloid (A␤)-induced inhibition of neurite outgrowth and synapse formation in a model of AD (Heredia et al, 2006;Petratos et al, 2008); and (4) RhoA/ROCK regulates fiber contraction by enhancing myosin light chain phosphorylation (p-MLC). In this way, RhoA/ROCK signaling, directly and/or indirectly activating MLC-kinase, phosphorylates MLC.…”
Section: Introductionmentioning
confidence: 99%